Evangelización waorani y violencia cultural en el Ecuador: 1956-2024 - Andrade, Susana M. (Pontificia Universidad Católica del Perú, 2025)
This article analyzes the Protestant evangelization process carried out by the Summer Institute of Linguistics among the Waorani of the Ecuadorian Amazon, from the arrival of American missionaries in 1954 to the present. Through oral testimonies, missionary documents, and ethnographic research, it examines the impact of evangelization on the Waorani people. The article argues that, under the discourse of salvation, a civilizing model was imposed that eroded key elements of traditional culture while enabling forms of economic and symbolic dependence. It also warns of the current risk of replicating this process with Indigenous peoples in voluntary isolation, through missions promoted by the evangelized Waorani. The article concludes that Waorani collective memory expresses both the traces of civilizational trauma and resistance to the drive for evangelization and cultural homogenization.

El artículo analiza el proceso de evangelización protestante llevado a cabo por el Instituto Lingüístico de Verano entre los waorani de la Amazonía ecuatoriana, desde la llegada de los misioneros estadounidenses en 1954 hasta la actualidad. A través de testimonios orales, documentos misioneros e investigación etnográfica, se examina el impacto de la evangelización en el pueblo waorani. El texto argumenta que, bajo el discurso de salvación, se impuso un modelo civilizatorio que erosionó elementos claves de la cultura tradicional, al tiempo que habilitó formas de dependencia económica y simbólica. Asimismo, se advierte el riesgo actual de replicar este proceso con los pueblos indígenas en aislamiento voluntario, mediante misiones promovidas por los waorani evangelizados. El artículo concluye que la memoria colectiva waorani expresa tanto las huellas del trauma civilizatorio como la resistencia frente al afán de evangelización y homogeneización cultural.
Waorani Evangelization and Cultural Violence in Ecuador: 1956-2024
Keywords: Waorani; Evangelization; Summer Institute of Linguistics; Cultural Contact; Evangelism; Waorani; Evangelización; Instituto Lingüístico de Verano; Contacto cultural; Evangelismo; https://purl.org/pe-repo/ocde/ford#5.04.03